Investment in Aceh (Such Factors Obstacle and Support and also Increasing Strategy of Investment Strategy) - Malahayatie,; Qorib, Ahmad; Siregar, Saparuddin (International Journal of Psychosocial Rehabilitation, 2020)
--Invesment is one of the important role in economic growth. The research has the purpose to :1) identify the cases that become to the obstacle and supoorted factors for investment in Aceh province. The kind of this research is qualitative research in term of arrange the the strategic policy that will be developed with the participatory approach from the stakeholder element with the bussiness man and private sector . The Sampling method is purposive sampling method to some informan of stakeholders and selected businessman. Furthermore the data was analysed using the SWOT and QSPM analysis and formulate the strategy and operational steps in increasing the invesment in Aceh Province. The result of this analysis showed the cases which is become to the obstacles factor for investment and they are : 1) Lack of the productive economic and it was shown by low of amount and of Processing industry in Aceh ; 2) the quality of human resources quality not supported to the direction of regional potential in that area; 3) the obstacles of Infrastructure and non infrastructure that still not maximum in taking the benefit and advantage; 4) The illegal cost or “pungli” still taken out of formal cost that become to the conditional; 5) Complicated and not transparant process of birocration and not straight to the target;6) Lack of careness of local bussinessman in Aceh to work on investment in priority sector in Aceh; 7) goverment local budgeting using still not straight to the target. The supported factor in this investment are ; 1) farming sector because Aceh was agro industry so the farming sector become to the priority; 2) Gardening Potential still dominated by coconut palm gardening; 3)other priority comoditysuch as coffee, cocoa, cloves and areca nut has potential value for growing the gardening comodities; 4) The development of infrastructure has shown the development; 5) Uderwater Tourism development through the syariah tourism (halal tourism); 6) potential sector of fishing and maritim; 7) the area of specific economic and area of Industry of Aceh. Some strategies were formulated so that will occur the increasing of invesment in Aceh that was ; 1)enlarge the production capacity; 2) revitalization of infrastructure that will support the production; 3) regulation statement that will support the bussiness world;4) increase the productivity of human resources; 5) support the development of agroindustry and processing in the region. After SWOT analysis has been done then also be strengthened by using the QSPM analysis by the result of analysis strategy and based on the highest result was ;1) increasing the productivity of human resource or labour quality 2) conducting all kind of promotion activity3) increasing the availability and quality of infrastucture 4) statement of law certainty 5) increasing the community participation and also security guaratee.